Redacted : The Archives of Censorship in Transwar Japan - Abel, Jonathan E., 1971- (Book collections on Project MUSE., 2012)
This study examines the contradictory relationships between preservation, production, and redaction to shed light on the dark valley attributed to wartime culture and to cast a shadow on the supposedly bright, open space of free postwar discourse.